2013
DOI: 10.1186/2194-3206-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Penetration capacity of the wood-decay fungus Physisporinus vitreus

Abstract: Purpose: Bioincising is a biotechnological process for improving the permeability of refractory wood such as Norway spruce heartwood using the wood-decay fungus Physisporinus vitreus. The degradation of the bordered pit membranes by P. vitreus in its first stage of wood colonization enhances the uptake of preservatives and wood modification substances, whereas the strength of the material is not significantly reduced. Methods:We propose to study bioincising by means of a mathematical model, because many factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Angiosperms also store a larger amount of extractives in parenchyma cells to avoid the spread of decay (Sun et al 2007;Morris et al 2016), whereas gymnosperm defence mainly relies on the occlusion of tracheids and abundant anti-fungal compounds produced by resin ducts (Fuhr et al 2013;Hudgins et al 2004). Interestingly, angiosperm species physically protect their wood by having a 1.3-fold higher wood density, mainly realised through thick-walled fibres than gymnosperms, whereas gymnosperms protect their wood by having a 2-fold higher lignin concentration than angiosperm species (cf.…”
Section: Conservative Gymnosperm Versus Acquisitive Angiosperm Speciesmentioning
confidence: 99%
“…Angiosperms also store a larger amount of extractives in parenchyma cells to avoid the spread of decay (Sun et al 2007;Morris et al 2016), whereas gymnosperm defence mainly relies on the occlusion of tracheids and abundant anti-fungal compounds produced by resin ducts (Fuhr et al 2013;Hudgins et al 2004). Interestingly, angiosperm species physically protect their wood by having a 1.3-fold higher wood density, mainly realised through thick-walled fibres than gymnosperms, whereas gymnosperms protect their wood by having a 2-fold higher lignin concentration than angiosperm species (cf.…”
Section: Conservative Gymnosperm Versus Acquisitive Angiosperm Speciesmentioning
confidence: 99%
“…Interestingly, another study across seven tree species from the Amazon found that high parenchyma abundance and wide dilating rays were associated with poor compartmentalisation of decay, but this was offset by fast wound closure (Romero & Bolker, 2008). Although in angiosperms, parenchyma cells in contact with vessels can seal off conduits by way of tyloses or gum deposits to avoid the spread of decay (Biggs, 1987;Bonsen & Ku cera, 1990;Schmitt & Liese, 1992;Sun et al, 2007), defence in gymnosperms mainly lies in the occlusion of tracheids via aspiration of the torus-margo bordered pits (Fuhr et al, 2013), and the production of abundant polyphenolic compounds and traumatic resin ducts in Pinaceae and Cupressaceae (Phillips, 1948;Hudgins et al, 2004). Such a strategy is therefore consistent with a lower RAP fraction in conifers.…”
Section: Rap Fractions As a Defence Systemmentioning
confidence: 99%
“…The winter-deciduous angiosperm species may require a high carbohydrate storage capacity to survive winter and flush new leaves in spring ( Epron et al, 2012 ), whereas the evergreen gymnosperms can flush new leaves later in spring using photosynthates coming from their preserved needles rather than stored carbohydrates ( Lusk, 2001 ). The parenchyma cells in angiosperms are also important to produce a large amount of extractives to avoid the spread of decay ( Sun et al, 2007 ; Morris et al, 2016 ), whereas gymnosperm defense relies more on the occlusion of tracheids and abundant antifungal compounds produced by resin ducts ( Hudgins et al, 2004 ; Fuhr et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%